Pengaruh Tingkat Pendidikan, Pengalaman Kerja Dan Kompetensi Akuntansi Terhadap Kualitas Laporan Keuangan UMKM di Kota Bogor - Sekar Arum Mawarni; Airin Nuraini (Institut Bisnis dan Informatika Kesatuan, 2021)
MSMEs are one of the drivers of economic development. With financial reports, MSME can obtain all kinds of financial information that is important for their business. The quality of financial reports can be done in two ways, the first method is related to research on the determinants that produce quality financial reporting. By studying this phenomenon, the focus on this method is related to the company’s internal factors related to its internal. The research method used is the first method, which is to see the quality of internal financial reports, namely human resources which includes educational level, work experience and accounting competence. This study is motivated by the inconsistency of the result of previous studies in different areas and several different variables, which may be due to other variables that play a role in relation. This study aims to determine the effect of educational level, work experience and accounting competence on the quality of financial reports on MSMEs in Bogor City. The research method used is quantitative research that is sourced from a questionnaire and is measured by Likert Scale. The population in this study were 50 respondents, who were taken from SMEs in the city of Bogor. MSMEs that used as data are MSMEs that record financial statements in their business. The data used are primary data. The data obtained were then analyzed using SPSS 21 program. The result showed in this study indicate that all the variables tested that is educational level, work experience, and accounting competence have a positive effect on the quality of MSME financial reports in Bogor City. Keywords: educational level, work experience, accounting competence, quality of financial reports.